2013
DOI: 10.1097/brs.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Versus Posterior Surgical Approaches to Treat Cervical Spondylotic Myelopathy

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(70 citation statements)
references
References 10 publications
4
66
0
Order By: Relevance
“…Moreover, compression in the present model is only mediated from posterior, whereas in human CSM it can occur selectively anterior, posterior, or circumferentially. The method of decompression in the present model is consistent with a posterior decompression in human patients, which has been shown to be comparable to anterior decompression in terms of post-operative outcome [15, 32]. …”
Section: Discussionsupporting
confidence: 62%
“…Moreover, compression in the present model is only mediated from posterior, whereas in human CSM it can occur selectively anterior, posterior, or circumferentially. The method of decompression in the present model is consistent with a posterior decompression in human patients, which has been shown to be comparable to anterior decompression in terms of post-operative outcome [15, 32]. …”
Section: Discussionsupporting
confidence: 62%
“…However, debate persists about selecting anterior or posterior approaches [491011]. Many studies have shown good clinical and radiological outcomes with anterior, posterior or combined approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown good clinical and radiological outcomes with anterior, posterior or combined approaches. Notwithstanding the general agreement about the most appropriate approach, such as posterior approach for multi-level involvement and anterior approach for kyphotic deformity, definite guidelines have not been established [911]. In some cases, radiological patterns have been used to select a surgical approach for cervical spondylotic myelopathy, although definite conclusions have never been reached [12].…”
Section: Discussionmentioning
confidence: 99%
“…12 Secondly, modern studies demonstrate improvement in mJOA and SF-36 PCS scores following surgery for CSM. 12,22 The mean mJOA scores for patients in the Kadanka studies did not improve following surgery and it is unclear what the reasons were for the lack of improvement.…”
Section: Comparative Studies - Mixed Results For Surgerymentioning
confidence: 99%
“…They observed a 2.5-3.5 point improvement in mJOA following surgery (regardless of approach) and also significant improvements in the SF-36 PCS scores. 22 Although non-operative treatment was not compared to surgical treatment in these studies, the number of patients studied was larger than previous RCTs and the study used validated outcomes tools to demonstrate the treatment effect of surgery.…”
Section: Modern Prospective Studiesmentioning
confidence: 99%